2018
DOI: 10.1002/erv.2609
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of mHealth interventions for the support of eating disorders

Abstract: Limited effects were found for mHealth interventions to reduce ED-related symptoms. A common evaluation framework for ED mHealth interventions should be proposed to assess the validity of interventions before implementing them on a larger scale in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0
33

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 46 publications
5
45
0
33
Order By: Relevance
“…Overall, the findings indicate that eTherapies for EDs, principally those intended for BN and BED phenotypes, successfully produced decreases in ED symptoms, and comorbid depression and anxiety at postassessment, with small to medium effect sizes. These results are supported by previous meta-analyses on eTherapies for EDs, which also demonstrate the effectiveness of digital interventions in reducing both ED and related symptoms (Aardoom et al, 2013;Anastasiadou et al, 2018;Dölemeyer et al, 2013;Melioli et al, 2016).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Overall, the findings indicate that eTherapies for EDs, principally those intended for BN and BED phenotypes, successfully produced decreases in ED symptoms, and comorbid depression and anxiety at postassessment, with small to medium effect sizes. These results are supported by previous meta-analyses on eTherapies for EDs, which also demonstrate the effectiveness of digital interventions in reducing both ED and related symptoms (Aardoom et al, 2013;Anastasiadou et al, 2018;Dölemeyer et al, 2013;Melioli et al, 2016).…”
Section: Discussionsupporting
confidence: 84%
“…eTherapy refers to the provision of targeted mental health interventions via information and communication technologies such as tablets, smartphones and computers, and often requires use of the internet (Aardoom, Dingemans, Spinhoven, & Van Furth, 2013). Several systematic reviews and meta-analyses have been published recently demonstrating the acceptability of eTherapies and their effectiveness in reducing eating disorder (ED) symptoms (Aardoom et al, 2013;Anastasiadou, Folkvord, & Lupiañez-Villanueva, 2018;Dölemeyer, Tietjen, Kersting, & Wagner, 2013;Hay & Claudino, 2015;Loucas et al, 2014;Melioli et al, 2016). However, while some reviews have concluded that the eTherapies evaluated to date offer a worthy alternative to traditional individual psychotherapy (Aardoom et al, 2013;Dölemeyer et al, 2013), others display greater scepticism and conclude that there is insufficient evidence to support the equivalence of eTherapies and the traditional model of treatment delivery (Hay & Claudino, 2015;Loucas et al, 2014).…”
mentioning
confidence: 99%
“…It allows for families to get support and reduces the stigma they may feel. Online‐ and e‐health measures for ED patients have been developed and tested for over 20 years worldwide and are available for implementation, but more research is necessary (Anastasiadou et al, ; Anderson et al, 2017; Barakat et al, ; Vollert et al, 2019; Zerwas et al, 2017). However, some aspects of the assessment can be challenging to monitor without face‐to‐face contact or some form of surrogate measure (Keshen et al, 2020; McLean et al, 2019), especially in more extreme cases (e.g., severely underweight, non‐suicidal self‐injury, self‐destructive patients).…”
Section: General Implications For Eating Disordersmentioning
confidence: 99%
“…We also know very little about the relative merits of book-based versus technologybased interventions. Recent advancements have led to an increase in mobile app-based programmes, although most of them are used for self-monitoring purposes 46 . Little is as yet known about the usability and feasibility of delivering mobile-based stand-alone self-help programmes.…”
Section: Research Implicationsmentioning
confidence: 99%